2013
DOI: 10.1146/annurev-economics-061109-080430
|View full text |Cite
|
Sign up to set email alerts
|

Price Rigidity: Microeconomic Evidence and Macroeconomic Implications

Abstract: We review recent evidence on price rigidity from the macroeconomics literature, and discuss how this evidence is used to inform macroeconomic modeling. Sluggish price adjustment is a leading explanation for large effects of demand shocks on output and, in particular, the effects of monetary policy on output. A recent influx of data on individual prices has greatly deepened macroeconomists' understanding of individual price dynamics. However, the analysis of these new data raise a host of new empirical issues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(92 citation statements)
references
References 120 publications
6
76
1
9
Order By: Relevance
“…Kaltenbrunner and Lochstoer (2010) and Croce (2012) document that long-run 8 Other recent contributions to this literature are Golosov and Lucas Jr. (2007), Klenow and Willis (2007), Kryvtsov (2008), Knotek II (2008), Eichenbaum, Jaimovich, and Rebelo (2011), Midrigan (2011), Anderson, Jaimovich, and Simester (2012, Kehoe and Midrigan (2012), Bhattarai and Schoenle (2012), Eichenbaum, Jaimovich, Rebelo, and Smith (2013), Kaplan andMenzio (2013), andVavra (2013). Klenow and Malin (2010) and Nakamura and Steinsson (2013) provide excellent reviews of the recent literature on price rigidity using micro price data.…”
Section: A2 Financementioning
confidence: 98%
“…Kaltenbrunner and Lochstoer (2010) and Croce (2012) document that long-run 8 Other recent contributions to this literature are Golosov and Lucas Jr. (2007), Klenow and Willis (2007), Kryvtsov (2008), Knotek II (2008), Eichenbaum, Jaimovich, and Rebelo (2011), Midrigan (2011), Anderson, Jaimovich, and Simester (2012, Kehoe and Midrigan (2012), Bhattarai and Schoenle (2012), Eichenbaum, Jaimovich, Rebelo, and Smith (2013), Kaplan andMenzio (2013), andVavra (2013). Klenow and Malin (2010) and Nakamura and Steinsson (2013) provide excellent reviews of the recent literature on price rigidity using micro price data.…”
Section: A2 Financementioning
confidence: 98%
“…A large literature documents short-term price stickiness and less than perfect pass-through of higher costs to consumers. (See, for example, Klenow and Kryvtsov (2008), Klenow and Malin (2010), Nakamura and Steinsson (2013), and Gopinath and Rigobon (2008)). …”
Section: Background On Foreign Currency Debtmentioning
confidence: 99%
“…1 Recent reviews of this literature can be found in Klenow and Malin (2010), Maćkowiak and Smets (2008) and Nakamura and Steinsson (2013 Gagnon and Lopez-Salido (2014). Defining prices in this way induces 'noise' in the data (see Eichenbaum et al, 2014) and about half of the price changes observed in the raw data are less than one penny.…”
Section: Description Of Price Datamentioning
confidence: 99%